Palm oil in salty snacks: A South African labelling audit on sustainability communication - Manzimase Sishi-Vilakazi; Henriette L. de Kock (South African Journal of Science)
Palm oil is widely used in global food production and is highly valued in the salty snack industry for its frying performance, oxidative stability and cost-effectiveness. However, concerns about its environmental and social impacts persist. We investigated the prevalence of palm oil and its derivatives in salty snack products, the presence of sustainability claims, including the Roundtable on Sustainable Palm Oil (RSPO) certification logo, and other types of claims on salty snack product labels. A total of 638 in-market products across six categories (maize, potato, grain, vegetable and fruit chips, and ready-to-eat popcorn) were audited. Palm oil and its derivatives were declared in 59% of products; 27% used alternative oils and 14% listed only ‘vegetable oil’ without specifying the oil type. Maize chips (45%) and potato chips (31%) were the largest product categories, with 60% and 69%, respectively, containing palm oil and its derivatives. Vegetable chips showed the lowest reliance on palm oil. Despite the prominence of palm oil, none of the products featured the RSPO certification logo or any certification indicating sustainable palm oil sourcing. Instead, product claims primarily highlighted dietary information, flavour characteristics and production methods. These findings reveal that while palm oil use is widespread in salty snacks, engagement with palm oil sustainability concerns is lacking. This gap presents an opportunity for manufacturers to adopt certified sustainable palm oil or eco-friendly alternatives, aligning with Sustainable Development Goal (SDG) 12 (responsible consumption and production) and growing consumer demand for transparency and environmental responsibility.